SISTEM PEMILIHAN KETUA DPD PDI PERJUANGAN JAWA TENGAH PERIODE 2013-2015 - Putro, Ferry Priyono; Utomo, Susilo; ., Fitriyah (Journal of Politic and Government Studies, 2014)
A political party is one of the agents in a system called democracy. The success of a party to run a democratic system we can see through the political recruitment function. PDI-P is one of the major parties in Central Java, which has a mass base a lot. Vacancy that occurs in the DPD PDIP must immediately be filled again by the political elite recruiting a new chairman to replace. This study used a descriptive study in which the analysis here will explain an object, phenomenon, or social background terejawantahkan research objectives in narrative writing. Research location in the city of Semarang where DPD PDIP located. Vacancy in the position of chairman of DPD PDIP become a matter of considerable interest to study, vacancy that occurs during the approaching election of the Governor of Central Java raises recruitment patterns of the political elite as well as the system used in the election of the chairman of PDI struggle to fill vacant positions. Through this study the authors tried to describe how the patterns of recruitment conducted by PDI-P to replace the Chairman of the Council, both for five-year periods as well as filling vacant positions as last occurred in 2013. Then the researchers here also to answer how the system is performed by the Chairman of the PDI PDI Struggle for the five-year period and filling vacant positions.